Force distribution of a cylindrical grip differs between dominant and nondominant hand in healthy subjects - Pingel, Isabel; Lorz, Daniel; Beier, Justus; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia (Archives of Orthopaedic and Trauma Surgery, 2018)
INTRODUCTION: Grip strength and load distribution of the hand are important parameters for evaluating hand function. The purpose of this study was to analyze and compare grip force and load distribution of dominant and nondominant hands in right-handed healthy subjects. METHODS: Gripping measurements were performed on 40 healthy right-handed subjects using a cylindrical gripping device. Two different cylinders with circumferences of 150 mm (small cylinder) and 200 mm (large cylinder), respectively, were used for the measurements. Subjects were assigned to either the small or the large cylinder with respect to their hand size. Maximum and mean force applied during three intervals of gripping as well as the percent contribution of each digit, thenar, and hypothenar in relation to the total load applied were acquired. Values of dominant and nondominant hands were compared. RESULTS: Percent contribution of mean grip strength differed for the thumb (p = 0.007), ring finger (p < 0.001), little finger (p = 0.047), and palm (p < 0.001). Comparing the dominant and nondominant side, the dominant hand showed a lower contribution of the thumb, ring finger, and little finger, but a higher contribution of the palm. When analyzing maximum grip, percent contribution of the small fingers was equal between dominant and nondominant side (p = 0.1). Differences between dominant and nondominant thumb, ring finger, and palm persisted (p = 0.007, p = 0.001, p = 0.005, respectively). No differences could be shown for the index finger, middle finger, thenar, and hypothenar when analyzing both mean and maximum force. DISCUSSION AND CONCLUSION: Percent contribution of the thumb and the fingers to total grip strength differed between dominant and nondominant hands with a change in distribution when assessing maximum grip force. In right-handed subjects, thumb and ring finger have important roles during gripping.
EVALuna2:211471

Prospective analysis of grip strength and load distribution after surgical treatment of common diseases of the hand with novel’s manugraphy® system - Grüner, Jasmin; Cai, Aijia; Pingel, Isabel; Horch, Raymund E.; Beier, Justus; Arkudas, Andreas (Archives of Orthopaedic and Trauma Surgery, 2023)
Background: Carpal tunnel syndrome, A1 annular pulley stenosis and Dupuytren’s contracture are among the most common conditions of the hand. In this study, we investigated the impact of surgical procedure on hand grip strength and high-resolution spatial load distribution in individuals suffering from those diseases over a follow-up period of one year. Materials and methods: In this prospective study, data of 9 patients with carpal tunnel syndrome, 12 patients with A1 annular pulley stenosis and 7 patients with Dupuytren’s contracture were evaluated. Only patients with unilateral disease were included providing the contralateral hand as an intra-individual control. Grip strength was measured with cylindrical instruments in two different sizes with respect to the hand size of the patients. Maximum and average values of grip strength as well as spatial load distribution in each finger, thenar, hypothenar and palm were analyzed. Data of the affected patients were collected preoperatively and 6 weeks, 6 months and 1 year postoperatively. Grip strength and spatial load distribution were compared preoperatively to postoperatively. In addition, DASH score, Levine score, 2-point discrimination and degree of flexion contracture were assessed. Results: The patients with A1 annular pulley stenosis showed a significant increase in grip strength 6 months and one year postoperatively. Patients with carpal tunnel syndrome and Dupuytren’s contracture showed no significant difference in grip strength over the course of time. An increase in the percentual grip strength of the thenar in patients with carpal tunnel disease and within the affected finger in A1 annular pulley stenosis was observed over the course of time. The DASH score was significantly lower in all patient cohorts one year postoperatively. Conclusion: Surgical procedure in carpal tunnel syndrome, A1 annular ligament stenosis and Dupuytren’s contracture improves the functionality of the hand in everyday life. Some areas of the hand seem to compensate other weaker areas in grip strength.
CRIS-Team Scopus Importer:2023-09-15
Keywords: A1 annular pulley stenosis; Carpal tunnel syndrome; Cylinder grip; Dupuytren’s contracture; Grip strength; Manugraphy